Good Apples : Behind Every Bite - Futrell, Susan, 1955- (Book collections on Project MUSE., 2017)
Apples are so ordinary and so ubiquitous that we often take them for granted. Yet it is surprisingly challenging to grow and sell such a common fruit. In fact, producing diverse, tasty apples for the market requires almost as much ingenuity and interdependence as building and maintaining a vibrant democracy. Understanding the geographic, ecological, and economic forces shaping the choices of apple growers, apple pickers, and apple buyers illuminates what's at stake in the way we organize our food system. Good Apples is for anyone who wants to go beyond the kitchen and backyard into the orchards, packing sheds, and cold storage rooms; into the laboratories and experiment stations; and into the warehouses, stockrooms, and marketing meetings, to better understand how we as citizens and eaters can sustain the farms that provide food for our communities. Susan Futrell has spent years working in sustainable food distribution, including more than a decade with apple growers. She shows us why sustaining family orchards, like family farms, may be essential to the soul of our nation.